Financial shocks and exchange market pressure - Ila Patnaik; Madhavi Pundit (Asian Development Bank (ADB), 2019)
The taper tantrum episode induced a sudden outflow of capital from emerging markets back to the United States. This paper analyzes exchange market pressure in 93 developing and emerging market economies during this episode, drawing on recent methodological improvements in measuring exchange market pressure. We find that all economies in the sample that were integrated with global capital markets were heavily hit. Although popular discourse suggested that the extent of an economy's fragility depended on its macroeconomic fundamentals, we find these fundamentals did not have much of a role in determining the level of pressure on a currency.
Keywords: E52; F31; F32; 330; capital flows; exchange market pressure; financial shock; international trade and finance; macroeconomics; taper tantrum